Partial TCR Signals Delivered by FcR-Nonbinding Anti-CD3 Monoclonal Antibodies Differentially Regulate Individual Th Subsets - Judith A. Smith; Qizhi Tang; Jeffrey A. Bluestone (1998)
Anti-CD3 mAbs with low FcR affinity prolong graft survival in the absence of the cytokine-mediated toxicity observed with conventional anti-CD3 treatment. Previous studies have shown that FcR-nonbinding anti-CD3 mAbs suppress immune responses, at least in part, by delivering a partial signal resulting in Th1 unresponsiveness. In this study, the biochemical and functional consequences of FcR-nonbinding anti-CD3 treatment for various activated T cell populations were examined. In contrast to Th1 cells, FcR-nonbinding anti-CD3-treated Th2 cells secreted IL-4 and proliferated. Furthermore, Th2 cells cultured with the mAb were not rendered unresponsive. Mixed "Th0" populations responded to FcR-nonbinding anti-CD3 by producing IL-4, and showed a selective decrease in IL-2 production following preculture with the mAb. The stimulation of IL-4-producing cells did not reflect a more complete TCR signal, since similar defects in zeta, ZAP-70, and MAP kinase phosphorylation were observed in Th1 and Th2 cells. Despite the proximal signaling defects, FcR-nonbinding anti-CD3 induced nuclear translocation of NF-ATc. Thus, Abs that deliver partial TCR signals may promote development of a Th2 phenotype during the course of an immune response via selective effects on different Th subsets.